Does Socioeconomic Inequality in Health Persist among Older People Living in Resource-Poor Urban Slums? - Falkingham, Jane C. (Springer US, 2011)
Using self-reported health that assesses functionality or disability status, this paper investigates whether there are any differences in health status among older people living in a deprived area of Nairobi, Kenya. Data from a cross-sectional survey of 2,037 men and women aged 50 years and older are used to examine the association between socioeconomic position and self-reported health status across 6 health domains. Education, occupation, a wealth index, and main source of livelihood are used to assess the presence of a socioeconomic gradient in health. All the indicators showed the expected negative association with health across some, but not all, of the disability domains. Nonetheless, differences based on occupation, the most commonly used indicators to examine health inequalities, were not statistically significant. Primary level of education was a significant factor for women but not for men; conversely, wealth status was associated with lower disability for both men and women. Older people dependent on their own sources of livelihood were also less likely to report a disability. The results suggest the need for further research to identify an appropriate socioeconomic classification that is sensitive in identifying poverty and deprivation among older people living in slums.